2011
DOI: 10.4314/ajcem.v12i3.7
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro efficacy of antimicrobial agents used in the treatment of bacterial eye infections in Ibadan, Nigeria

Abstract: Failure to cure eye infections, and reduced potency in topical antimicrobials had been observed in South Western Nigeria, this study sought to evaluate in vitro, the efficacy of antimicrobial agents in the treatment of ocular infections. A total of 46 ocular bacterial isolates were recovered from the diagnostic laboratory of the University College Hospital, Ibadan, from conjunctival swabs of patients having underlying eye diseases (Cataracts, glaucoma and esotrapia), and from patients presenting with other sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…The Staphylococcus aureus was noted in general to be the most common isolate among all the ocular infections observed in this study which is corroborated by various other studies in India and abroad by M. J. (1,2,8,9,10) The most common fungal aetiology among all the ocular infections revealed in this study was Aspergillus species. The fungal agents responsible for individual ocular infective conditions in this study revealed that Aspergillus (32.6%) were the most common fungal isolates from keratitis cases, in dacryocystitis Candida albicans (4.34%) was the most common isolate followed by Aspergillus fumigatus (2.18%); in conjunctivitis, only Candida albicans was isolated; no fungal pathogen was isolated from other ocular infections.…”
Section: Discussionsupporting
confidence: 89%
“…The Staphylococcus aureus was noted in general to be the most common isolate among all the ocular infections observed in this study which is corroborated by various other studies in India and abroad by M. J. (1,2,8,9,10) The most common fungal aetiology among all the ocular infections revealed in this study was Aspergillus species. The fungal agents responsible for individual ocular infective conditions in this study revealed that Aspergillus (32.6%) were the most common fungal isolates from keratitis cases, in dacryocystitis Candida albicans (4.34%) was the most common isolate followed by Aspergillus fumigatus (2.18%); in conjunctivitis, only Candida albicans was isolated; no fungal pathogen was isolated from other ocular infections.…”
Section: Discussionsupporting
confidence: 89%
“…From the public health point of view, coagulase negative staphylococci have been identified as the etiological agent in various infections and are among the microorganisms most frequently isolated in nosocomial infections (Cunha et al, 2006). Also, CNS have been implicated in infective endocarditis (Patel et al, 2000), prosthetic joint infections (Trampuz and Zimmerli, 2005), neonatal septiceamia (Ghelbi et al, 2008), Enterotoxins production (Veras et al, 2008) and bacterial eye infections (Ogbolu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1 Even though CoNS are usually considered innocuous, they are frequently associated with nosocomial infections, leading to greater interest in them as relevant pathogens rather than mere contaminants. 1,2 Bacterial eye infections, 3 prosthetic joint infections, 4 urinary tract infections (UTIs) especially among immunocompromised patients, 5 surgical site infections, 6 infective endocarditis 7 and cattle mastitis 8 are some conditions that have been associated with CoNS. 9 Because CoNS usually form part of the microbiota of the skin and mucous membranes, proper differentiation between clinically significant and contaminant bacteria is important in bacterial etiology of suspected infections.…”
Section: Introductionmentioning
confidence: 99%